DEVELOPING ENGLISH MODULE FOR HOSPITALITY STUDENTS USING INQUIRY-BASED LANGUAGE LEARNING IN BALIKPAPAN STATE POLYTECHNIC - Elizabeth Milaningrum; Patria Rahmawaty (UNIVERSITAS MUHAMMADIYAH METRO (MUHAMMADIYAH UNIVERSITY OF METRO), 2019)
This research is aimed at developing the existing English module for hospitality students to fulfill the students' needs in learning English using inquiry-based language learning at Balikpapan State Polytechnic. This research was conducted in the second semester of hospitality students at Balikpapan State Polytechnic. The research methodology used in this research was a research and development (R & D) for developing supplementary existing English module for hospitality students using IBLL. There are two stages of R & D study: (1) exploration stage which consists of library research, document analysis, and needs analysis. The purpose of the exploration stage is to find out the weaknesses of the existing English module by conducting documents analysis and to find out the students' need towards English materials by conducting an interview and delivering questionnaire. The result of reveals as follows: (a) the students need ESP (English for Specific Purposes ) materials; (b) the contents of the existing module are too general, only focus on TOEFL preparation and do not correspond with students’ need and integrated English skills; (c) the procedure of the existing module only focus on lecturer center ; and (2) development stage which is purposed to design the supplementary existing English module through several processes: (a) designing prototype based on the result of exploration stage; (b) experts validation; (c) trying out the prototype; (d) final revision. The data was taken from expert validation form, questionnaire, focus group discussion (FGD), and classroom observation. The data was analyzed by using an interactive method. The result shows that supplementary existing English module for Hospitality student is suitable to use in higher vocational education.